Pengawasan Pengelolaan Lingkungan Dibidang Pertambangan Berdasarkan Undang-Undang No. 4 Tahun 2009 Tentang Pertambangan Mineral dan Batu Bara - Eren Arif Budiman; Ahmad Arif Zulfikar (Universitas Batanghari Jambi, 2020)
One of the environmental issues that affect the management of natural resources is mining activities. Based on Law No. 4 of 2009 concerning Mineral and Coal Mining began to open new horizons regarding the juridical aspects of mining management from its environmental aspects as well as being discussed about the independence of Indonesian mining. The role of the government in the formulation of environmental management supervisory policies must be optimized because natural resources have a very important role, especially in the context of increasing state revenue through clear and fair mechanisms of taxes, levies and profit sharing, and protection from ecological disasters. In line with regional autonomy, the gradual delegation of authority from the central government to regional governments in natural resource management is intended to increase the role of local communities and maintain environmental functions. The method in this research is normative legal research. The source of law used in this research is secondary legal material obtained by conducting literature review. Data analysis in this research is by qualitative analysis. Based on the contents of the discussion related to the supervision of environmental management in the mining sector based on Law no. 4 of 2009 concerning Mineral and Coal Mining covering environmental management, reclamation and post-mining including environmental management and monitoring in accordance with environmental management documents or environmental permits that are owned and have been approved; arrangement, restoration and improvement of land in accordance with its allocation; stipulation and disbursement of reclamation guarantee; post mining management; stipulation and disbursement of post-mining guarantees; and compliance with environmental quality standards in accordance with statutory provisions.